2021
DOI: 10.12659/msm.933385
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between the Modified External Fixation and Calcaneal Traction in Ruedi-Allgower Type II/III Pilon Fractures

Abstract: Background To compare the effect of modified external fixation and calcaneal traction in a staged management of Ruedi-Allgower type II/III tibial pilon fractures. Material/Methods The data of 62 patients with Ruedi-Allgower type II/III tibial pilon fractures who were treated in Liuzhou People’s hospital from January 2017 to December 2018 were extracted in this retrospective analysis. There were 32 patients in the temporary external fixation (TEF) group and 30 patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, our study has already showed that no significant differences were found either 2.0 mm diameter Kirschner wires or 3.5 mm diameter Steinmann pins used, in terms of traction weight, effectiveness of swelling reduction, length of preoperative traction duration and pain relief, but lower incidence and shorter duration of post-traction bleeding, as well as faster wounds healing, were definitely observed with the use of thinner traction pins. Given our study’s validation of the safety and efficacy of 2.0 mm diameter Kirschner wires for skeletal traction, and considering the elevated rates of pin tract infections reported with larger diameter traction pins in other studies 3 , 13 , in which 4.0 mm or lager diameter traction pins were used 3 , 13 , we advocate for the use of 2.0 mm diameter Kirschner wires in skeletal traction procedures.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…However, our study has already showed that no significant differences were found either 2.0 mm diameter Kirschner wires or 3.5 mm diameter Steinmann pins used, in terms of traction weight, effectiveness of swelling reduction, length of preoperative traction duration and pain relief, but lower incidence and shorter duration of post-traction bleeding, as well as faster wounds healing, were definitely observed with the use of thinner traction pins. Given our study’s validation of the safety and efficacy of 2.0 mm diameter Kirschner wires for skeletal traction, and considering the elevated rates of pin tract infections reported with larger diameter traction pins in other studies 3 , 13 , in which 4.0 mm or lager diameter traction pins were used 3 , 13 , we advocate for the use of 2.0 mm diameter Kirschner wires in skeletal traction procedures.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies have demonstrated that these management techniques can significantly enhance patients' prognosis 4 , 6 12 . While previous studies have predominantly focused on evaluating the clinical impact of preoperative temporary external fixation, limited research has directly compared the effectiveness of skin traction, skeletal traction, and external fixation 3 , 4 , 13 , 14 . Moreover, studies examining the differences in efficacy among different diameter traction pins in skeletal traction are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several techniques have been introduced for the initial treatment of severe fractures, such as external xator xation, splint xation, and calcaneal traction. Typically, these techniques have been applied to complex tibial plateau fractures, pilon fractures, and other severe injuries [17][18][19][20]. A paradigm shift has been achieved by adding ankle fracture-dislocations to the indications for two-stage management.…”
Section: Discussionmentioning
confidence: 99%